Stock Price Adjustments to Quarterly Earnings Announcements : A· Test of Semi-Strong form of Market Efficiency - Iqbal; Mallikarjunappa, T.; Nayak, Panduranga (Gyan Management Journal, 2007)
Debate on stock market efficiency has been continuing. This paper examines semi-strong form of market efficiency by aking March 200lquarterly earnings nouncement as an event. The study is ased on 150 companies having 20 percent or above foreign holding. We. ave used both raw returns and log returns. The results revealed that under market model with raw returns a erage abnormal returns (AARs) are negative for 27 days and positive for 34 days. Under market model with log returns AARs